Intra-urban patterns of neighborhood-level social capital: a pilot study - Jaron King; Cassidy A. Hine; Tessa Washburn; Hunter D Montgomery; Robert A. Chaney (Tabriz University of Medical Sciences, 2019)
Background: Social capital is a construct of interaction and social trust in one's fellow community members. These interactions can provide a safety net for individuals in terms of information, social support, and adherence to social norms. While a number of studies have previously examined the relationship between social capital and health outcomes, few have examined the theparallel relationship of social capital and geographic "place" with respect to health outcomes. Methods: Considering social capital as facilitated by specific structures, we evaluate the relationship between neighborhood-level social capital and disability rates in a major Southern US city. Disability rates were collected through neighborhood-level data via the AmericanCommunity Survey (ACS) and compared to a geocoded map of neighborhood-level social capital measures during spring, 2016. Results: Higher social capital within a neighborhood coincided with lower disability rates in that neighborhood (r=-0.14, P=0.016) when compared to random assortment models. Conclusion: Findings from this research add evidence to the value of the built environment, not only providing resources and shaping choices, but for facilitating important social relationships.